Thematic Interpretation: Thematic Study of the Verse on Environmental Conservation in QS. Al-A'raf: 56 - Abdul Hayyaqdhan Asufah; Hasyim Haddade; Muhammad Irham (Aslama: Journal of Islamic Studies, 2026)
The global environmental crisis, marked by natural resource exploitation, pollution, and ecosystem degradation, calls for a robust ethical and normative framework. In Islamic thought, human beings are regarded as khalīfah fī al-arḍ, entrusted with the responsibility to protect the earth and prohibited from causing fasād (destruction). This article examines environmental conservation from a Qur’anic perspective, focusing on the principle of iṣlāḥ (rectification) and the ethical implications of Q.S. al-A‘rāf (7):56. The verse emphasizes the prohibition of environmental damage after the earth has been set in order and highlights a spiritual balance between fear and hope toward God. The discussion indicates that environmental preservation in Islam extends beyond ecological concerns to encompass moral, social, and spiritual responsibilities rooted in faith. Consequently, environmental stewardship is understood as both a manifestation of divine trust and a form of worship aimed at sustaining life for present and future generations.